The JPEX scandal: a test case for Hong Kong’s new cryptocurrency regulatory regime or is it still the wild west? - Lo, Noble Po Kan; Lau, Tony Hon Yiu (Frontiers in Blockchain, 2025)
This paper inves gates the challenges and effec veness of Hong Kong's regulatory framework for digital assets and cryptocurrencies in the wake of the JPEX Scandal. The scandal serves as the first significant test of the city's regulatory measures aimed at protec ng consumers and investors from fraudulent ac vi es within the crypto space. The study delves into the background and development of blockchain technology and cryptocurrencies, highligh ng their rapid evolu on and the associated regulatory challenges. By examining the JPEX case, the paper evaluates the robustness of Hong Kong's regulatory tools and their ability to balance consumer protec on with fostering innova on. The paper employs a doctrinal legal methodology, supplemented by a case study of JPEX, to assess whether the current regulatory framework is adequate or if further adjustments are required. The findings suggest that while significant strides have been made, certain gaps remain, par cularly concerning decentralised finance (DeFi) and decentralised autonomous organisa ons (DAOs). The paper concludes with recommenda ons for enhancing regulatory clarity and ensuring the sustainable growth of Hong Kong as a global crypto hub.